2011
DOI: 10.1128/jvi.00173-11
|View full text |Cite
|
Sign up to set email alerts
|

Rab5 and Class III Phosphoinositide 3-Kinase Vps34 Are Involved in Hepatitis C Virus NS4B-Induced Autophagy

Abstract: Autophagy has been shown to facilitate replication or production of hepatitis C virus (HCV); nevertheless, how HCV induces autophagy remains unclear. Here, we demonstrate that HCV nonstructural protein 4B (NS4B) alone can induce autophagy signaling; amino acid residues 1 to 190 of NS4B are sufficient for this induction. Further studies showed that the phosphorylation levels of S6K and 4E-BP1 were not altered, suggesting that the mTOR/S6 kinase pathway and mTOR/4E-BP1 pathway did not contribute to NS4B-or HCV-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
127
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(133 citation statements)
references
References 51 publications
5
127
1
Order By: Relevance
“…Of these proteins, Rab5 and Rab7 play major roles in endocytic vesicle trafficking (24)(25)(26)(27)(28). Rab5 and Rab7 are involved in the life cycles of multiple viruses in the family Flaviviridae, such as hepatitis C virus (HCV) (29,30), dengue virus (DNV), and West Nile virus (WNV) (31,32). Virus infection strongly depends on Rab5 and/or Rab7 expression; depletion of Rab5 and/or Rab7 hampers virus replication, indicating that virus transport from early to mature endosomes is a required step in the viral life cycle.…”
mentioning
confidence: 99%
“…Of these proteins, Rab5 and Rab7 play major roles in endocytic vesicle trafficking (24)(25)(26)(27)(28). Rab5 and Rab7 are involved in the life cycles of multiple viruses in the family Flaviviridae, such as hepatitis C virus (HCV) (29,30), dengue virus (DNV), and West Nile virus (WNV) (31,32). Virus infection strongly depends on Rab5 and/or Rab7 expression; depletion of Rab5 and/or Rab7 hampers virus replication, indicating that virus transport from early to mature endosomes is a required step in the viral life cycle.…”
mentioning
confidence: 99%
“…Some viruses regulate mTOR signaling to control autophagy (6,25,38,56). HCV induces autophagy through the Rab5 and class III PI3K Vps34 pathway (55). Human immunodeficiency virus inhibits autophagy through the Src-Akt and STAT3 pathway (59).…”
mentioning
confidence: 99%
“…The dependence of BEFV on early and late endosomes suggests that virus must be able to reach bona fide late endosomes for fusion and release from the endocytic pathway. Rab5 and Rab7 have also been demonstrated to regulate autophagy and maturation of late autophagic vacuoles, respectively (23,35). Previously, several studies demonstrated that autophagosomes or autophagic vacuoles fuse with early and late endosomes (1,25) as well as lysosome (11,22).…”
Section: Discussionmentioning
confidence: 99%